DEVELOPMENT OF DOCUMENTARY FILM MEDIA ON WATER POLLUTION MATERIALS TO SUPPORT SCIENCE LEARNING IN JUNIOR HIGH SCHOOLS - Febiola Pastika Sari; Masriani Masriani; Rahmat Rasmawan; Rachmat Sahputra; Rody Putra Sartika (Sean Institute, 2022)
This research is about a documentary film of water pollution that can improve student learning outcomes with contextual learning involving the dual senses, namely the sense of hearing and the sense of sight. This study aims to determine the feasibility of water pollution documentary film media to support science learning in junior high schools. This research is based on observations and interviews of teachers and students. The research method used is Research and Development (R&D) with the ADDIE development model the stages used are analysis, design and development. The subject in the study was a documentary film of water pollution. Data collection techniques in this study used direct communication during interviews with teachers and students as well as indirect communication in the form of instrument feasibility assessment sheets, media feasibility validation questionnaires consisting of 3 media experts and 3 material experts. This study shows that the validation results carried out obtained a percentage for the media aspect of 91.63 and the material aspect of 86.13 from this percentage result, it can be concluded that the media is suitable for use at the implementation stage.